A Philosophical Critique of Cognitive Psychology's Definition of the "Person.". - FULLER, ROSA TURRISI (Pluralist)
The article provides an analysis of how the person is defined in cognitive psychology. It features a discussion on Thomas Nagel's paper called "What Is It Like to Be a Bat?" as well as David Chalmers' concept of the human mind. The article also presents how Renee Descartes' idea of the conscious mind contradicts with that of Chalmers'.